PENGGUNAAN STRATEGI BERTANYA OLEH MAHASISWA PENDIDIKAN BAHASA INGGRIS UNP PADANG DALAM PRAKTIK MICRO TEACHING - Saun, Saunir (English Department FBS UNP, 2015)
The application of the questioning skills (both the basic and advanced questioning skills) is very important in teaching because they play an important role in arising the studentsâ€™ attention and thinking which, at last, ditermine the studentsâ€™ understanding and mastery of the lessons they learn. However, this research found that many of the students in a micro teaching class could not use the questioning strategies well. This paper shows and discusses the application of the strategies used by the students of English in a micro teaching practice in an Englsh class.Â Keywords: Strategi bertanya, pendidikan bahasa Inggris, Micro Teaching